x+2*x+2*x+2*x+2+11=49

Simple and best practice solution for x+2*x+2*x+2*x+2+11=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2*x+2*x+2*x+2+11=49 equation:


Simplifying
x + 2x + 2x + 2x + 2 + 11 = 49

Reorder the terms:
2 + 11 + x + 2x + 2x + 2x = 49

Combine like terms: 2 + 11 = 13
13 + x + 2x + 2x + 2x = 49

Combine like terms: x + 2x = 3x
13 + 3x + 2x + 2x = 49

Combine like terms: 3x + 2x = 5x
13 + 5x + 2x = 49

Combine like terms: 5x + 2x = 7x
13 + 7x = 49

Solving
13 + 7x = 49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 7x = 49 + -13

Combine like terms: 13 + -13 = 0
0 + 7x = 49 + -13
7x = 49 + -13

Combine like terms: 49 + -13 = 36
7x = 36

Divide each side by '7'.
x = 5.142857143

Simplifying
x = 5.142857143

See similar equations:

| x+1/3-x+2/4=x+1 | | 7x+5-2x+1=4x+8 | | 9x^4-16x^2=0 | | 6-4v+4=v+5 | | 0=2(2x^3+3x^2+7x-5) | | 14x+140=147+13 | | 3t+21= | | x^2+19x-216=0 | | 2x+2(x-20)=212 | | n^4-9n^2=0 | | 3(0.3-4.5v)=-32.1-7.5v | | 3x^2-36=(3x-2)(x-2) | | x(5x+10)=0 | | x=-1+2y | | 2(m-3)=6 | | 5x-9x+12=-2x+6 | | 0=4x^2+11x-3 | | x^2-5x-8=-6x-2 | | 4(c-2)=7(c+1) | | 50n^3-2n=0 | | 7-6x=31 | | x^2+x-13=7 | | 9*7+8*3= | | 2(m-3)=-12 | | 45x(4+3)=1000 | | (6a-2)(5a-4)= | | w(9+-1w^2)= | | 7(5x+3)=x+21 | | 4*7-5= | | 22M-4N=24 | | 45x(4x+3)=1000 | | 27a^2-3=0 |

Equations solver categories